2021
DOI: 10.1111/jcmm.16524
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐derived exosomes mediate silica‐induced pulmonary fibrosis by activating fibroblast in an endoplasmic reticulum stress‐dependent manner

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…EVs have been isolated from silica-exposed Mφ and found to induce the proliferation of myofibroblasts and fibroblasts and increase their expression levels of SPP1 ( 36 ). They also induce the overproduction of proinflammatory cytokines and promote myofibroblast activation in an endoplasmic reticulum stress-dependent manner ( 30 ).…”
Section: Immunomodulatory Effects Of Mφ-evs In Chronic Inflammatory Diseasementioning
confidence: 99%
“…EVs have been isolated from silica-exposed Mφ and found to induce the proliferation of myofibroblasts and fibroblasts and increase their expression levels of SPP1 ( 36 ). They also induce the overproduction of proinflammatory cytokines and promote myofibroblast activation in an endoplasmic reticulum stress-dependent manner ( 30 ).…”
Section: Immunomodulatory Effects Of Mφ-evs In Chronic Inflammatory Diseasementioning
confidence: 99%
“…PFD has proven its anti-inflammatory, antioxidant, and anti-fibrotic effects in many fibrotic diseases. Since PFD reduced the severity of silicosis by inhibiting the epithelial mesenchymal transition (EMT), regulating the TGF-β 1/Smad2/3 signaling pathway ( Wang et al, 2020 ; Qin et al, 2021 ), and inhibiting the production of IL-17A (24), we used it as a positive control in our study. AKEX0011 is not inferior to PFD in the prevention and treatment of silicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no M2 polarization under silica stimulation in vitro , various in vitro experiments have shown that silica can facilitate the secretion of pro-fibrotic factors in macrophages to aggravate pulmonary fibrosis ( Pang et al, 2021 ). Silica-exposed macrophage-derived exosomes can activate fibroblasts to proliferate and to express collagen I and α-SMA ( Wang et al, 2020 ; Qin et al, 2021 ). Our experiments also proved that silica can induce macrophages secreting TGF-β, and AKEX0011 can alleviate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that EVs secretion increases in the supernatant of silica (SiO 2 )-stimulated macrophage. Moreover, lung fibroblasts incubated with these EVs are differentiated into myofibroblasts by inducing endoplasmic reticulum stress, which results in a significant increase in proliferation, migration, and expression of fibrotic proteins, such as collagen I and α-SMA [ 57 ]. Besides, recently, it was reported that miR-125a-5p is upregulated in EVs of silica (SiO 2 )-stimulated macrophage, and when lung fibroblasts are incubated with these EVs, α-SMA is overexpressed, and TGF-β is activated to mediate their differentiation into myofibroblasts through downregulation of Smurf1 [ 58 ].…”
Section: Evs and Their Involvement In Cellular And Molecular Mechanis...mentioning
confidence: 99%